1993
DOI: 10.1007/bf00420265
|View full text |Cite
|
Sign up to set email alerts
|

An unusual stress fracture of the lateral tibial plateau

Abstract: Stress fracture of the lateral tibial plateau is a rare occurrence. In this article we report a case of stress fracture of the lateral tibial plateau with a radiolucent fracture line in a 52-year-old man. To our knowledge, such a case has not yet been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In general, medial tibial plateau stress fractures are more common than stress fractures of the lateral tibial plateau[16,17]. Mizuta et al[16] reported a case of the lateral tibial plateau stress fracture, which was associated with knee valgus angulation with 92 degrees of medial tibial slope on radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, medial tibial plateau stress fractures are more common than stress fractures of the lateral tibial plateau[16,17]. Mizuta et al[16] reported a case of the lateral tibial plateau stress fracture, which was associated with knee valgus angulation with 92 degrees of medial tibial slope on radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Mizuta et al[16] reported a case of the lateral tibial plateau stress fracture, which was associated with knee valgus angulation with 92 degrees of medial tibial slope on radiographs. Hashemi et al[8] described that the lateral-to-medial slope of the tibial plateau, which they used the term “coronal tibial slope”, ranged between -1°and 6°, whereas the only one subject had a coronal tibial slope of 91° in normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,7,11 Anterior cortex stress fractures often require surgical intervention such as excision and bone grafting or intramedullary nailing to achieve union. 2,7 Although there have been several reports of isolated medial and lateral tibial plateau stress fractures, 5,10 there is little in the literature with regard to anterior proximal metaphysial tibial stress fractures. There are 2 reports of basketball players with anterior proximal tibial stress fractures just distal to the tibial tuberosity.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,7,11 Stress fractures of the posteromedial tibial shaft and proximal tibial metaphysis are common and have been reported to heal readily with rest. 3,4,6,7 Although there are reports of isolated stress fractures of the medial or lateral tibial plateau, 5,10 there is little mention in the literature regarding stress fractures of the anterior proximal tibial metaphysis. 1,8 We report on a basketball player with a recurrent, complete stress fracture of the proximal tibial metaphysis.…”
mentioning
confidence: 99%